A review on organophosphorus toxicity in the farmers of solapur district from India - Kale, Bhagwat (International Journal of Biological Research, 2014)
Organophosphorus compounds were first developed by scientist Schrader shortly before and during Second World War. They were first used as agricultural insecticides and later as potential chemical warfare agent. A great proportion of acute poisoning cases are caused by exposure to these pesticides. Pesticides can enter the body through the skin (dermal), mouth (oral), lungs (breathing), and eyes (ocular) and due to accidental ingestion.  It is found that the Organophosphorus compound, dimethoate is more commonly used to attempt suicide as it is easily available and cheap. 54 % poisoning cases were observed only due to dimethoate. The poisoning due to warfarin, tick-20, chlorpyrifos, fenthion, thymate and lice powder is less common. Acute Organophosphorus poisoning leads to paralysis of skeletal muscles. Paralysis generally occurs in between 48 to 72 hours after poisoning and is associated with cranial and proximal limb muscle weakness. Inability to lift the neck, inability to sit up, opthalmoparesis, slow eye movements, facial weakness, difficulty in swallowing, limb weakness (proximal is more than distal), areflexia, respiratory failure etc. are clinical features of paralysis. These features together are called as intermediate syndrome. On other hand, organophosphorus poisoning is also associated with respiratory failure. Respiratory failure occurs due to many reasons, such as central respiratory depression, respiratory muscle weakness, bronchospasm, bronchorrhea, aspiration of gastric contents, anorexic brain damage etc. This togetherly is associated with Acute Respiratory Distress Syndrome (ARDS). Identification of poisoning is done on the basis of symptoms shown by patients while perfect diagnosis requires biochemical analysis. Symptoms such as hyper-salivation, convulsions, respiratory failure, ataxia, slurred speech, miosis, muscle cramping suggest about poisoning. To access Organophosphorus poisoning, it is necessary to analyze biological samples mostly blood and urine.          Organophosphorus compounds can be detected in urine however, their degradation is rapid and hence their detection in urine is possible for short time. The detection of metabolites of Organophosphorus compounds is another way to detect Organophosphorus poisoning. Metabolites circulate for longer time and mostly excreted in urine. Detection of metabolites of Organophosphorus compounds is always better than detection of parent compound in blood or urine. This is because parent compound has short life time and its detection is not possible for more than hours after poisoning. For some Organophosphorus compounds (e.g. Parathion, Paraoxon), detection of              P–nitrophenol in urine is an indicator of Organophosphorus poisoning. Recently, antibodies against Organophosphorus compounds in blood are also detected. Thus, blood and urine remains main source for biological and biochemical examination in Organophosphorus poisoning. Most commonly, detection of Organophosphorus poisoning is done by estimating activities of enzymes namely Acetyl         Cholinesterase, Butyryl Cholinesterase and Acylpeptide Hydrolase from blood. All these enzymes contains serine residue at their         catalytic sites. Organophosphorus compound binds with this serine residue and inactivates the enzymes. Such inactivation of above       enzymes is only concerned with Organophosphorus poisoning and thus inhibition of Acetyl Cholinesterase, Butyryl cholinesterase and Acylpeptide Hydrolase is highly correlated with severity and duration of poisoning with Organophosphorus   compounds. Keywords: Organophosphorus, Acetyl Cholinesterase, Butyryl Cholinesterase, Pest, ARDS Etc.